Alternativas para el Control Multivariable (2015)
This paper presents multiple alternatives for multivariable control in two industrial processes: Distillation Column and Evaporator. The design of four control strategies is presented, that includes a multiloop control, a decoupling multivariable control, both with Proportional Integral structure, a decoupling control through Inverse Nyquist Array, an Internal Model Control and a predictive control. Simulations results are obtained using Matlab, and show the potentialities of each one of those strategies to handle references changes and disturbances. The advantages of predictive control in regulation of multivariable processes are evident.